2009
DOI: 10.1186/cc7996
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Medical Emergency Team: the importance of dose

Abstract: Up to 17% of hospital admissions are complicated by serious adverse events unrelated to the patients presenting medical condition. Rapid Response Teams (RRTs) review patients during early phase of deterioration to reduce patient morbidity and mortality. However, reports of the efficacy of these teams are varied. The aims of this article were to explore the concept of RRT dose, to assess whether RRT dose improves patient outcomes, and to assess whether there is evidence that inclusion of a physician in the team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
3
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(170 citation statements)
references
References 35 publications
3
159
3
5
Order By: Relevance
“…There are typically fewer than 10 cardiac arrests per 1000 patient admissions [3][4][5]; however, mature RRTs review at least 20 patients per 1000 admissions [6] and a dose-response relationship between increasing RRT review rates and reducing cardiac arrests has been demonstrated [7]. RRTs also play a leading part in developing a safety-focused culture and patient-safety systems across hospitals, although it takes time for systems to mature, for barriers to be overcome, and for escalation of at-risk patients and learning from adverse events to become routine practice.…”
Section: Rrts Reduce the Incidence Of In-hospital Cardiac Arrestsmentioning
confidence: 99%
“…There are typically fewer than 10 cardiac arrests per 1000 patient admissions [3][4][5]; however, mature RRTs review at least 20 patients per 1000 admissions [6] and a dose-response relationship between increasing RRT review rates and reducing cardiac arrests has been demonstrated [7]. RRTs also play a leading part in developing a safety-focused culture and patient-safety systems across hospitals, although it takes time for systems to mature, for barriers to be overcome, and for escalation of at-risk patients and learning from adverse events to become routine practice.…”
Section: Rrts Reduce the Incidence Of In-hospital Cardiac Arrestsmentioning
confidence: 99%
“…Still, the level 1 evidence adds weight to the accumulating level 2-5 evidence and is sufficient to support implementation [10, 68, 78•, 79]. Beyond having a RRT, there is evidence in adults for a "dose-response" of RRT with 1 cardiac arrest potentially prevented for every 17 RRT calls [80]. That is, the more RRT calls, the greater reductions in CPA and mortality.…”
Section: Evidence For Rrtmentioning
confidence: 99%
“…RRT success also appears to be linked to practice; if the RRT is widely adopted by clinicians, it appears more effective. 35,36 A higher call intensity, or "dose rate," more than 25 RRT calls per 1000 admissions, is reported to be associated with decreases in cardiac arrest rate, 37 and conversely when the RRT rate decreases, the cardiac arrest rate increases. 36 The RRT must be used to be effective, and if it is not used, benefits may not be manifested.…”
Section: Impact Of Rrts On Patients' Outcomesmentioning
confidence: 99%